2004
DOI: 10.1021/bi048551f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure ofEscherichia coliArnA (PmrI) Decarboxylase Domain. A Key Enzyme for Lipid A Modification with 4-Amino-4-deoxy-l-arabinose and Polymyxin Resistance,

Abstract: Gram-negative bacteria including Escherichia coli, Salmonella typhimurium, and Pseudomonas aeruginosa can modify the structure of lipid A in their outer membrane with 4-amino-4-deoxy-Larabinose (Ara4N). Such modification results in resistance to cationic antimicrobial peptides of the innate immune system and antibiotics such as polymyxin. ArnA is a key enzyme in the lipid A modification pathway, and its deletion abolishes both the Ara4N-lipid A modification and polymyxin resistance. ArnA is a bifunctional enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 54 publications
4
94
0
2
Order By: Relevance
“…2B69) is unpublished; however, two research groups have independently published analyses of the structure (PDB ID no. 1U9J and 2BLL) of the C-terminal portion of E. coli ArnA (18,42). The C-terminal portion of this bifunctional enzyme catalyzes the NAD ϩ -dependent oxidative decarboxylation of UDPGlcA as part of a pathway leading to production of UDP-4-amino-4-deoxy-L-arabinose (7,18,42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B69) is unpublished; however, two research groups have independently published analyses of the structure (PDB ID no. 1U9J and 2BLL) of the C-terminal portion of E. coli ArnA (18,42). The C-terminal portion of this bifunctional enzyme catalyzes the NAD ϩ -dependent oxidative decarboxylation of UDPGlcA as part of a pathway leading to production of UDP-4-amino-4-deoxy-L-arabinose (7,18,42).…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal portion of this bifunctional enzyme catalyzes the NAD ϩ -dependent oxidative decarboxylation of UDPGlcA as part of a pathway leading to production of UDP-4-amino-4-deoxy-L-arabinose (7,18,42). Analysis of the crystal structure of the C-terminal decarboxylase region of ArnA revealed that R 619 and S 433 are important for decarboxylase activity (7,18,42). In addition, site-directed mutations of S433A, E434A, and E434Q of ArnA affected UDP-GlcA decarboxylase activity.…”
Section: Resultsmentioning
confidence: 99%
“…This protein is found in most Gram-negative bacteria and catalyzes the decarboxylation of UDP-glucuronic acid to UDP-4-keto-arabinose by adding a formyl group. The modified arabinose, which is then attached to lipid A, is essential for resistance to cationic antimicrobial peptides such as polymyxin (66)(67)(68). The second protein is an outer membrane protein (OmpF), and its function is limited to the passive diffusion of small molecules across the outer membrane pores (69).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the function of ArnA in the oxidative decarboxylation of UDP-GlcUA. All three proteins possess the conserved glycine-rich "Rossmann fold," located within the first 13 amino acids of the dTDP-D-glucose 4,6-dehydratase and UDP-galactose epimerase (52,53) and between Arg-317 and Gly-330 of ArnA (55).…”
Section: One-dimensional 1 H Nmr Spectroscopy Of the Formylated Produmentioning
confidence: 99%